Distribution, Occupancy, and Habitat of the Endangered Carolina Madtom: Implications for Recovery of an Endemic Stream Fish - W. Robert Cope; Thomas J. Kwak; Tyler R. Black; Krishna Pacifici; Jennifer M. Archambault; W. Gregory Cope (Fishes, 2024)
Endemic fish are important components of freshwater ecosystems because they contribute to biodiversity and provide vital ecological functions. The Carolina Madtom, Noturus furiosus, is a small catfish endemic to the Neuse and Tar river basins of North Carolina, USA. Three previous surveys over the past 60 years have shown declining occurrence and abundance in the basins, and as such, the species was listed as federally endangered in 2021. To provide critical information to guide Carolina Madtom conservation and recovery strategies, we surveyed 36 sites (75 locations) in both basins to (1) determine the current distribution of the Carolina Madtom, (2) develop occupancy models to estimate probability of detection and occurrence of the species throughout its range, and (3) determine its instream habitat use and suitability. We collected 59 Carolina Madtom during snorkel surveys in the Tar River basin and none from the Neuse River basin, indicating that Carolina Madtom populations are still declining in both occurrence and abundance throughout their historical and recent range, especially in the Neuse River basin. Occupancy modeling estimated low occupancy probability (0.35), while detection probability was high (0.81). Carolina Madtom occupied slow-to-moderate velocity water over sand and gravel substrate, using cobble and woody debris as cover. Habitat suitability distributions quantified the most suitable ranges of microhabitat parameters for Carolina Madtom occupancy. A comparison of available suitable habitat in the two river basins revealed that adequate suitable habitat was available in both basins, suggesting that other factors such as pollution or predation from the non-native Flathead Catfish Pylodictis olivaris, may be contributing to population declines. The application of our results will aid in management and recovery actions for the species.